2009
DOI: 10.1109/lawp.2009.2024561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pedestrian Movement on MIMO-OFDM Channel Capacity in an Indoor Environment

Abstract: Effects of pedestrian movement on multipleinput-multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) channel capacity have been investigated using experiment and simulation. The experiment was conducted at 5.2 GHz by a MIMO-OFDM packet transmission demonstrator using four transmitters and four receivers built in-house. Geometric optics-based ray-tracing technique was used to simulate the experimental scenarios. Changes in the channel capacity dynamic range have been analyzed for different num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…The spectral efficiency (SE) of a MIMO system without the knowledge of the channel at the transmitter can be calculated as [33]: SE=j=1Ntitaliclog2(1+EbRγjNoBNt)where γ j is the eigen value of HnHnH, Hn=NrHitalicForbeniusH is the normalized channel matrix [34], and (.) H denotes Hermitian transpose.…”
Section: Parametric Modeling Of System Characteristicsmentioning
confidence: 99%
“…The spectral efficiency (SE) of a MIMO system without the knowledge of the channel at the transmitter can be calculated as [33]: SE=j=1Ntitaliclog2(1+EbRγjNoBNt)where γ j is the eigen value of HnHnH, Hn=NrHitalicForbeniusH is the normalized channel matrix [34], and (.) H denotes Hermitian transpose.…”
Section: Parametric Modeling Of System Characteristicsmentioning
confidence: 99%
“…This corresponds to the system where co-channel interference is the limiting factor for the system capacity, and enough Tx power is reserved to cater every location within the coverage area. Several research papers [12][13][14][15][16] have been presented based on the finding of the project. In addition, with the presented outcome, one of the main ideas of this paper is to combine the investigations and present a systematic study of the MIMO-OFDM channel study for populated indoor environment.…”
Section: Mimo-ofdm Channel Capacitymentioning
confidence: 99%
“…Rayleigh and Rice distributions are special cases of the Nakagami distribution when the Nakagami parameter (m) is 1 and greater than 1, respectively. The Rayleigh and Rice probability density functions are given by (4) and (5), respectively. This dependency on the value of m means that the Nakagami distribution is likely to be seen as a much more general model for environments where there are large spatial changes in the amount of scattering from one position to another.…”
Section: Path Loss and Small-scale Variationmentioning
confidence: 99%
“…Research such as that performed by Chen and Dubey [3] have incorporated temporary aspects into their models, but this is usually limited to transceiver movement rather than the movement of people in the channel. More recently Gupta et al [4] have investigated the effect of people movement on the channel response. They found that the presence of people in the propagation channel can increase channel capacity as well as reduce it.…”
Section: Introductionmentioning
confidence: 99%